An age of iron and rust Cassius Dio and the history of his time - Scott, Andrew G. ca. 20./21. Jh (Brill, 2023)
Cassius Dio described his own age as one of 'iron and rust'? This study, which is the first of its kind in English, examines the decline and decay that Cassius Dio diagnosed in this period (180-229 CE) through an analysis of the author's historiographic method and narrative construction. It shows that the final books were a crucial part of Dio's work, and it explains how Dio approached a period that he considered unworthy of history in view of his larger historiographic project
Keywords: Cassius -- Dio -- 163-235 -- Historia Romana; Cassius Dio Cocceianus / Roman history; Rome / History / Empire, 284-476 / Historiography; Roman history (Cassius Dio Cocceianus); Historiography; Rome (Empire); 284-476; History